Abortion learning mechanisms for nurses and midwives: a scoping review of evidence - Martha Nicholson; Lesley Hoggart (Sexual and Reproductive Health Matters)
Access to safe, affordable, and supported abortion care is a crucial component of reproductive justice and human rights. Abortion seekers consider nurses and midwives to be more supportive than other health professionals. Nurses and midwives have long been recommended providers of comprehensive abortion care, including second trimester care. This iterative scoping review aimed to explore the evidence on abortion learning mechanisms available to nurses and midwives and what can be improved about abortion training. Using the Arksey and O’Malley (Scoping studies: towards a methodological framework. Int J Soc Res Methodol. 2005;8(1): 19-32) and Levac et al. (Scoping studies: advancing the methodology. Implement Sci. 2010;5(1): 69) scoping review frameworks, four databases were searched, resulting in 879 articles published in English from 01.01.2010 to 01.08.2024. The authors included 43 studies and identified five learning mechanisms. The evidence is presented under three themes: (1) the adequacy of abortion learning mechanisms for nurses and midwives, (2) listening to nurses and midwives’ experiences, and (3) barriers to abortion training. This review found that in almost all legal and practice contexts, abortion training may be de-prioritised and hard to access because of institutional barriers, especially in centres of education. In conclusion, there is a low investment in abortion training for nurses and midwives. Policy-makers, health care systems, and educators should consider ways to continuously instil nurses and midwives with skills, confidence, and social authority to provide person-centred abortion care to combat harmful bias and mitigate the risk of reproductive coercion.